Netizens' comments on an Indonesian news social media platform 'Detikcom' : A microstructure analysis - Silaban, Rizky Dewita; Pulungan, Anni Holila; Ginting, Immanuel Prasetya (Journal of Language and Pragmatics Studies, 2024)
Netizens are active internet users who communicate, express opinions, and collaborate on internet media. This study discussed netizens comments on the Indonesian news social media platform Detikcom. The objectives of this study are to examine the types of microstructures in netizens’ comments about the news on Detikcom twitter, to illustrate the realization of microstructures aspect, and to explain the reasons microstructures aspect realized in netizens’ comments about a news on Detikcom Twitter (X). A qualitative descriptive approach was applied to this study. The data source is netizens’ comments on Detikcom Twitter (X). The data sources were the netizens’comments on Detikcom Twitter (X). The data were analyzed using Van Dijk theory about Critical Discourse Analysis. The findings show that there are types of microstructures that is included in the netizens’ comments of Mario Dandy news on Detikcom Twitter (X) they are semantic, stylistica, rethoric, and syntactic. The reason for the microstructure aspects realized in netizens’ comment were to depict the types of microstructures on the news, to interpret netizens’ comments using the microstructure theory, and to involve knowledge in capturing different information from the netizens’ comments as a part of critical discourse analysis.